Upaya Membangun Eksistensi Lembaga Pendidikan Islam di Masyarakat Melalui Madrasah Diniyah Takmiliyah Awaliyah - Wahid, Rosid; Syahidin, Syahidin; Fakhruddin, Agus (PAKAR Pendidikan, 2024)
The various problems among elementary school students are caused by several factors, especially the lack of religious education that children receive. This phenomenon indicates that Islamic religious education cannot carry this responsibility alone. Therefore, attention to MDTA is understandable, primarily since the institution focuses on Religion and Religious Education as regulated in PP 55 of 2007. The research aims to describe Madrasah Diniyah Takmiliyah Awaliyah, aspects of the curriculum implemented by MDTA, members owned by MDTA, infrastructure owned by MDTA, finances contained in MDTA, and MDTA's relationship with the community. The research was conducted using a qualitative approach with exploratory methods. The results of this research inform that to make MDTA superior. An explicit curriculum is needed to implement the provisions set by the Ministry of Religion; apart from that, it also requires complete personnel ready to realize MDTA educational goals. MDTA institutions must also always pay attention to learning facilities as superior institutions. MDTA does not only depend on assistance provided by the Ministry of Religion and City/Regional Government but also through community self-help. MDTA's relationship with the community is established through support and involvement from the environment around MDTA. Based on research conducted, MDTA has an ecosystem that can support students' religious education. Therefore, the researcher recommends examining other levels of education at Madrasah Diniyah Takmiliyah to determine the sustainability of the benefits that MDTA students can obtain.